Parental concerns regarding a centre-based early intervention programme for Down syndrome in Malaysia: A case study - Kunagaratnam, N.; Loh, S.C. (Springer, 2010)
This qualitative study provides information on the concerns faced by parents having children with Down syndrome in a centre-based Early Intervention Programme in Malaysia and how they coped with these concerns. Semi-structured interviews were conducted with a total of five parents and two special educators. The interview and observation findings indicate that there are numerous concerns faced by parents, such as the child's uncertain future, teacher training, family involvement, expansion of services, support services, lack of information and resources, inconsistency of language used, increase in fees, and changes in lifestyle. The study has also revealed unmet needs of special children, for example, time duration, music therapy and the facilities provided. Recommendations have also been suggested for further needed improvement in the Early Intervention Programme.